KLASIFIKASI KARAKTERISTIK DAMPAK INDUSTRI PADA KAWASAN PERMUKIMAN TERDAMPAK INDUSTRI DI CEMANI KABUPATEN SUKOHARJO - Desita Putri Pradani; Murtanti Jani Rahayu; Rufia Andisetyana Putri (Universitas Sebelas Maret Surakarta, 2017)
Abstract:.Cemani Village/kelurahan Cemani is one of regions in Kecamatan Sukoharjo, which is one of the industrial area. as listed in Sukoharjo Regional Spatial Plan year 2014, Cemani village located around the huge industrial company such as Batik Keris compan,Dan Liris company, Konimex company, and Sobisco company. The problem in this research is how is the classification characteristics of industrial area and how it affected residential areas of Sukoharjo Cemani? The purpose of this study was to determine the classification of the characteristics of industrial impacts on residential areas that affected by industrial areea at Cemani Sukoharjo. The method used is the deductive research methods with quantitative research. Technique of analysis that used is descriptive analysis. This research conclusion is the impacts of the major industries in Sukoharjo Cemani settlement are: the emergence of the settlement of labor / industrial workers, the emergence of slum area, water pollution and flood the area. Cassification of this bad impacts of the industrial area to the physical environment can be perceived by people’s settlement in 0-500 m> 500m - 1kilometer, and> 1 kilometer from the industrial area. Keywords: Industrial Impact, Industrial Impact Classification, Industrial Settlement Areas